2018
DOI: 10.1124/mol.117.110775
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Reversal of Oxycodone Tolerance in Dorsal Root Ganglia Neurons

Abstract: Oxycodone is a semisynthetic opioid compound that is widely prescribed, used, and abused today, and has a well-established role in shaping the current opioid epidemic. Previously, we have shown that tolerance develops to the antinociceptive and respiratory depressive effects of oxycodone in mice, and that a moderate dose of acute ethanol or a protein kinase C (PKC) inhibitor reversed that tolerance. To investigate further if tolerance was occurring through neuronal mechanisms, our aims for this study were to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Morphine, in particular, is known to preferentially induce PKC-mediated MOR phosphorylation, which has been implicated in the mechanism of in vivo tolerance to antinociception (Smith et al, 1999(Smith et al, , 2006Inoue and Ueda, 2000;Hua et al, 2002;Kliewer et al, 2019) and cellular tolerance in DRG (Jacob et al, 2018) and locus coeruleus neurons (Levitt and Williams, 2012;Arttamangkul et al, 2018). The present study showed that PKC mediates morphine tolerance to small intestinal transit in vivo and in myenteric plexus neurons.…”
Section: Discussionsupporting
confidence: 57%
“…Morphine, in particular, is known to preferentially induce PKC-mediated MOR phosphorylation, which has been implicated in the mechanism of in vivo tolerance to antinociception (Smith et al, 1999(Smith et al, , 2006Inoue and Ueda, 2000;Hua et al, 2002;Kliewer et al, 2019) and cellular tolerance in DRG (Jacob et al, 2018) and locus coeruleus neurons (Levitt and Williams, 2012;Arttamangkul et al, 2018). The present study showed that PKC mediates morphine tolerance to small intestinal transit in vivo and in myenteric plexus neurons.…”
Section: Discussionsupporting
confidence: 57%
“…All data are presented as mean ± s.e.m. Statistical comparison made by One-way ANOVA (C) with Bonferroni’s comparison (F (DFn, DFd—F ( 3 , 20 ) = 0.570). * indicates p < 0.05 as shown.…”
Section: Figurementioning
confidence: 99%
“…We have previously reported that in mice a low dose of ethanol, which by itself did not depress respiration, rapidly reversed tolerance to both morphine-and oxycodone-induced respiratory depression as well as tolerance to their antinociceptive effects (16)(17)(18)(19)(20) but did not reverse tolerance induced by methadone (17). We also observed that a low concentration of ethanol (20 mM) could reverse μ opioid receptor (MOR) desensitization and cellular tolerance to morphine in locus coeruleus (LC) neurons as well as tolerance to oxycodone in dorsal root ganglion neurons (20,21). Ethanol also reduced the phosphorylation of MOR induced by morphine (21).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that in mice acute, low doses of ethanol rapidly reverse tolerance to the respiratory depressant and analgesic effects of morphine and oxycodone (Hull et al, 2013, Hill et al, 2016, Jacob et al, 2017, Hill et al, 2018 but do not reverse tolerance induced by methadone (Hill et al, 2016). Reversal of morphine tolerance by a low concentration of ethanol (20 mM) can also be observed at the single neuron level in vitro (Llorente et al, 2013, Jacob et al, 2018 indicating that the effect is at the level of cells -opioid receptors to reverse receptor desensitization, rather than an action to alter drug disposition in the brain.…”
Section: Introductionmentioning
confidence: 99%